2001
DOI: 10.1002/mds.1050
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of eyeblink classical conditioning in progressive supranuclear palsy

Abstract: In a previous study we showed that learning in eyeblink classical conditioning (EBCC) is normal in Parkinson's disease (PD) and that the serial reaction time task (SRTT) is only marginally impaired. Since pathological lesions are more widespread in the atypical parkinsonian disorder of progressive supranuclear palsy (PSP) than in PD, we hypothesized that PSP patients may show more profound deficits in the EBCC and SRTT learning tasks. We therefore investigated EBCC with a delay and two trace paradigms, an SRTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Schugens et al (2000) concluded that damage to cerebellar nuclei appears likely in most of these studies. In one study of progressive supranuclear palsy (Sommer et al 2001) where eyeblink conditioning was completely absent, it was concluded that the critical damage was to the cerebellar dentate-interpositus nuclear region.…”
Section: Cerebellar Interpositus Nucleus Lesionsmentioning
confidence: 99%
“…Schugens et al (2000) concluded that damage to cerebellar nuclei appears likely in most of these studies. In one study of progressive supranuclear palsy (Sommer et al 2001) where eyeblink conditioning was completely absent, it was concluded that the critical damage was to the cerebellar dentate-interpositus nuclear region.…”
Section: Cerebellar Interpositus Nucleus Lesionsmentioning
confidence: 99%
“…The procedures were virtually identical to and detailed in the earlier studies from our group 12 14. In brief, an unconditioned stimulus (UCS), that is, an electric pulse over the supraorbital nerve, invariably induces an eyeblink reflex.…”
Section: Methodsmentioning
confidence: 99%
“…Electromyographic (EMG) activity was recorded using silver-silverchloride cup electrodes fixed with adhesive tape over the lower eyelid (active electrode) and over the ipsilateral temple (reference electrode); with a sampling rate of 10 kHz 12 14. EMG signals were fed into a recording device and filtered at 100 Hz and 5 kHz (SynAmps, Neuroscan Inc, Virginia, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations